Analisis Pengaruh Kualitas Produk, Kualitas Layanan, dan Citra Merek terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan sebagai Variabel Intervening (Studi pada Klinik Kecantikan Cosmedic Semarang) - Dennisa, Eugenia Andrea; Santoso, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2016)
This research was conducted with the background on the phenomenon of the amount number of complaints. Increased number of complaints will lead to dissatisfied customer and will affect to customer loyalty. The purpose of this research is to determine the influence of product quality, service quality, and brand image in influencing customer satisfaction, in order to increase customer loyalty of Klinik Kecantikan Cosmedic’s Semarang customers. The research was conducted by taking samples using non probability sampling technique, which has ever visited and brought product/taking treatment in Klinik Kecantikan Cosmedic Semarang. The collection of data obtained from 150 customers of Klinik Kecanikan Cosmedic Semarang by filling questionnaire. Test method is a Maximum Likelihood analysis with Amos program version 21.0. The analysis showed that quality product, service quality, and brand image are giving positive and significant influence on customer satisfaction.As well as the quality product, service quality, and brand image are giving positive and significant influence on customer loyalty.And customer satisfaction is also giving positive and significant influence to customer loyalty.